PO185 Epigenetics bridges the genetic-environmental gap in parkinson's disease. (1st December 2017) - Shueb, Akrem; Blundell, Renald; DeWeerdt, Len; Sanchez, David
Abstract : Parkinson's disease (PD) is a complex multifactorial disease with an elusive aetiology, in which genetic and environmental factors are intricately associated. In recent years, epigenetic mechanisms such as DNA methylation, histone modifications and non-coding RNAs have been recognised as potential mediators in the pathogenesis of PD. Epigenetics refers to the heritable changes in gene expression that do not involve changes to the underlying DNA sequence. These modifications exist throughout our lifetime, commencing in the prenatal phase, and are influenced by the summation of one's genome and the environmental factors we are subjected to, rendering epigenetics as the missing link between the risk factors for PD and its development. Current pharmacological agents only provide symptomatic relief. Over the past few years, there has been a substantial progression in the development of epigenetic drugs particularly the HDACs and DNMTs inhibitors, as a novel therapeutic modality in the management of PD. Cell replacement therapy is a promising avenue for the treatment of PD with scientific research making great progress in the development of induced pluripotent stem cells to produce midbrain dopamine phenotypes. With direct access to the neurons that are affected in PD, the pace of discovery should speed up and the cure for PD should become an attainable goal. This comprehensive critical appraisal will shed light on the emerging role of epigenetics in the pathogenesis and therapeutic modulation of PD.